Anti-sweatshop movements vs mulinational companies : how pressure groups can change a company's ethical and marketing behavior? - Favre, Anaïs; Dimmitt, Nicholas J.; Swierczek, Fredric William; Zimmermann, Willi (Pathum Thani, Thailand : Asian Institute of Technology, 2006)
This study shows the way anti-sweatshop activism manage to change the labor standards in developing countries, and what are the actions still to be taken to improve it further and eradicate the sweatshop issue. It also studied the multinational companies' responses to the pressures they were subjected. on an ethical point of view, and especially the codes of conduct that were adopted. which are more precisely studied. Finally, it gives an overview of the current labor issues (child labor. right to unionize, work time, wages) and suggests some more recommendations for further improvements
Submitted in partial fulfillment of the requirements for the degree of Master of Business Administration
Keywords: Sweatshops -- Marketing